Physical load and heart rate behavior in workers in the slaughterhouse and meat packing industries - Santos, Lorena Altafin [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Garrigou, Alain; Pasquereau, Pierrick; Messias, Iracimara de Anchieta [UNESP] (FapUNIFESP (SciELO), 2023)
High physical overload during the workday and some conditions present in the workplace can generate several losses in the worker’s health. The use of tools capable of identifying physical load (PL), such as heart rate (HR) analysis, is essential. The aim of the study was to evaluate the physical load and heart rate behavior of workers in the slaughterhouse. The cardiovascular load reached by two individuals was 12% and 24%. In relation to the PL rating, they fit as moderately heavy to heavy work. The HR, was higher at the end of the work when compared to the beginning. Furthermore, it was pointed out that the temperature, noise, and body mass index were above normality values. The physical workload was classified as moderately heavy to heavy. The limit HR was reached in some moments of the work by one of the workers and two of them reached higher HR values at the end of the work.
Carga física e comportamento da frequência cardíaca em trabalhadores de frigorífico
Keywords: Animal culling; Ergonomics; Heart rate